European Surveillance System on Contact Allergies (ESSCA): contact allergies in relation to body sites in patients with allergic contact dermatitis - Oosterhaven, Jart; Uter, Wolfgang; Aberer, Werner; Armario‐Hita, José C.; Ballmer‐Weber, Barbara K.; Bauer, Andrea; Czarnecka‐Operacz, Magdalena; Elsner, Peter; García‐Gavín, Juan; Giménez‐Arnau, Ana M.; John, Swen M.; Kręcisz, Beata; et al. (Contact dermatitis, 2019)
Background Analyses of the European Surveillance System on Contact Allergies (ESSCA) database have focused primarily on the prevalence of contact allergies to the European baseline series, both overall and in subgroups of patients. However, affected body sites have hitherto not been addressed. Objective To determine the prevalence of contact allergies for distinct body sites in patients with allergic contact dermatitis (ACD). Methods Analysis of data collected by the ESSCA (www.essca-dc.org) in consecutively patch tested patients, from 2009 to 2014, in eight European countries was performed. Cases were selected on the basis of the presence of minimally one positive patch test reaction to the baseline series, and a final diagnosis of ACD attributed to only one body site. Results Six thousand two hundred and fifty-five cases were analysed. The head and hand were the most common single sites that ACD was attributed to. Differences between countries were seen for several body sites. Nickel, fragrance mix I, cobalt and methylchloroisothiazolinone/methylisothiazolinone were the most frequent allergens reported for various body sites. Conclusions Distinct allergen patterns per body site were observed. However, contact allergies were probably not always relevant for the dermatitis that patients presented with. The possibility of linking positive patch test reactions to relevance, along with affected body sites, should be a useful addition to patch test documentation systems.
First published: 05 December 2018
Gesehen am 21.08.2019